Rewriting the equation, you have 8t + -7t= -11 plus -6, so you get ( t= -17) (ans)
2006-11-10 12:39:28
·
answer #1
·
answered by WC 7
·
1⤊
1⤋
Simplifying
8t + 11 = 7t + -6
Reorder the terms:
11 + 8t = 7t + -6
Reorder the terms:
11 + 8t = -6 + 7t
Solving
11 + 8t = -6 + 7t
Solving for variable 't'.
Move all terms containing t to the left, all other terms to the right.
Add '-7t' to each side of the equation.
11 + 8t + -7t = -6 + 7t + -7t
Combine like terms: 8t + -7t = 1t
11 + 1t = -6 + 7t + -7t
Combine like terms: 7t + -7t = 0
11 + 1t = -6 + 0
11 + 1t = -6
Add '-11' to each side of the equation.
11 + -11 + 1t = -6 + -11
Combine like terms: 11 + -11 = 0
0 + 1t = -6 + -11
1t = -6 + -11
Combine like terms: -6 + -11 = -17
1t = -17
Divide each side by '1'.
t = -17
Simplifying
t = -17
2006-11-10 20:44:48
·
answer #2
·
answered by buzz kill 3
·
0⤊
0⤋
8t + 11 = 7t - 6
8t + 11 - 7t = 7t - 6 - 7t
t + 11 = - 6
t + 11 - 11 = - 6 - 11
t = - 17
The answer is t = - 17
- - - - - -s-
2006-11-11 08:39:10
·
answer #3
·
answered by SAMUEL D 7
·
0⤊
0⤋
t=17
First u subtract 7t from 8t, and 11 from -6.You should get t=17.
2006-11-10 20:39:22
·
answer #4
·
answered by Leandro 2
·
1⤊
2⤋
8t + 11 = 7t - 6
8t - 7t = -6 - 11
t = -17
2006-11-10 20:43:15
·
answer #5
·
answered by Anonymous
·
1⤊
0⤋
t=5
2006-11-10 21:07:14
·
answer #6
·
answered by cherry 2
·
0⤊
0⤋
8t + 11 = 7t - 6
t + 11 = -6
t = -17
2006-11-10 20:39:29
·
answer #7
·
answered by lady of the piano 3
·
1⤊
1⤋
8t+11=7t-6
- 11 -11
-------------------
8t+0=7t-17
8t=7t-17
-7t -7t
1t=-17
t= -17
2006-11-10 20:42:02
·
answer #8
·
answered by Tara84 1
·
0⤊
0⤋
t = -17
2006-11-10 21:43:18
·
answer #9
·
answered by J 6
·
0⤊
0⤋
t = -17
2006-11-10 20:41:36
·
answer #10
·
answered by JawaBoy 2
·
0⤊
0⤋